New technologies for managing industrial innovation funding - V. M. Zotov; N. M. Abdikeev (Финансы: теория и практика, 2021)
The subject of the study is new technologies for managing industrial innovation funding. The aim of the article is to form an optimal mechanism for the application of technologies for managing industrial innovation funding based on the use of new financial instruments. The relevance of the research is due to the increasing role of innovation in ensuring competitive advantages and market stability of industrial enterprises, as well as the growing need to attract funding. The scientific novelty consists in grouping the existing financing technologies into three main groups: traditional, modern and new. The research methods are analysis, systematization, synthesis, induction, deduction, modeling. The authors built a model of the mutual influence of innovative industrial development and the subsequent development of financing technologies in the financial sector. In the course of the study, the author obtained the following results: a mechanism for applying new technologies to manage innovation funding was developed, a priority financial instrument was identified for use within the framework of the developed mechanism. The authors conclude that the role of digital technologies in the activities of an industrial enterprise and, accordingly, in innovation funding is increasing. At the same time, the activities of an enterprise in attracting resources by issuing digital securities (shares) to finance innovations are of the greatest practical interest.